Phosphodiesterase-4 inhibitor in the treatment of psoriasis and psoriatic arthritis - O. Yu. Olisova; D. A. Svistunova; L. M. Chernyavskaya; E. M. Anpilogova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Treatment of psoriasis and psoriatic arthritis, especially moderate and severe, represents difficulties. Recently, various methods of molecular medicine have been actively developed, however, targeted therapy deserves special attention, which consists of chemical agents that have specific target as a specific protein or enzyme. Targeted therapy is a promising direction in many branches of medicine, especially in dermatology.Despite the wide range of biological products, their use may be accompanied by an increased risk of infectious processes and malignant neoplasms, which makes the search for a new pharmacological solution in targeted therapy even more relevant.This review presents the possibilities and prospects for the therapeutic use of the phosphodiesterase-4 inhibitor from the group of small molecules - apremilast, primarily in the treatment of psoriasis and psoriatic arthritis.